1998
DOI: 10.1104/pp.117.2.501
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Deprivation Induces Synchronous Golgi Differentiation in Suspension-Cultured Tobacco BY-2 Cells1

Abstract: To date, the lack of a method for inducing plant cells and their Golgi stacks to differentiate in a synchronous manner has made it difficult to characterize the nature and extent of Golgi retailoring in biochemical terms. Here we report that auxin deprivation can be used to induce a uniform population of suspension-cultured tobacco (Nicotiana tabacum cv BY-2) cells to differentiate synchronously during a 4-d period. Upon removal of auxin, the cells stop dividing, undergo elongation, and differentiate in a mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 53 publications
5
36
0
6
Order By: Relevance
“…As shown in Fig. 5A, the addition of 2,4-D to auxin-starved cells induced division within 3 h, confirming the timing and the absolute values of increase in mitotic index as previously described (23). YkB (1 M) completely inhibited cell division induced by 2,4-D, and cells entered stasis (Fig.…”
Section: Ykb Inhibition Links Aux/iaa Stability To Auxin-regulated Cesupporting
confidence: 89%
See 1 more Smart Citation
“…As shown in Fig. 5A, the addition of 2,4-D to auxin-starved cells induced division within 3 h, confirming the timing and the absolute values of increase in mitotic index as previously described (23). YkB (1 M) completely inhibited cell division induced by 2,4-D, and cells entered stasis (Fig.…”
Section: Ykb Inhibition Links Aux/iaa Stability To Auxin-regulated Cesupporting
confidence: 89%
“…Deprivation of auxin stops cell division and reveals the underlying cell elongation. Readdition of auxin stimulates division in a semisynchronous manner (23). As shown in Fig.…”
Section: Ykb Inhibition Links Aux/iaa Stability To Auxin-regulated Cementioning
confidence: 98%
“…Moreover, it was found that the amyloplast formation in BY-2 cells was always accompanied by a reduction in cell multiplication rate, increase in cell volume , shorter lifetime, weaker cell-cell adhesion (Sakai et al 2004a), and alterations in the secretion properties (unpublished result). The changes observed under amyloplst-inducing conditions resembles to what observed during differentiation of root cap cells, as has been suggested from the study of Golgi differentiation (Staehelin et al 1990, Winicur et al 1998. Thus, the behavior of BY-2 cells under amyloplast-inducing conditions (in the absence of auxin) might mimic the process of differentiation of the cells in the root cap, whereas the behavior under normal culture condition (in the presence of auxin) might mimic the process of cell proliferation in the meristem (Sakai et al 2004a).…”
Section: Amyloplast Differentiation In By-2 Cells: Similarity To Rootsupporting
confidence: 67%
“…Readdition of auxin stimulates division in a semisynchronous manner (Winicur et al, 1998). As shown in Figure 4A, the cell division in auxin-starved cells was initiated by the addition of 2,4-D within 3 h as described previously (Winicur et al, 1998). Application of 20 mM TrfA completely inhibited cell division induced by 2,4-D and cells entered stasis (Fig.…”
Section: Trfa Inhibits Auxin-dependent Cell Divisionmentioning
confidence: 60%
“…Cell division of BY2 cultured cells is critically dependent on auxin and is interrupted by auxin deprivation. Readdition of auxin stimulates division in a semisynchronous manner (Winicur et al, 1998). As shown in Figure 4A, the cell division in auxin-starved cells was initiated by the addition of 2,4-D within 3 h as described previously (Winicur et al, 1998).…”
Section: Trfa Inhibits Auxin-dependent Cell Divisionmentioning
confidence: 94%